FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI POLA USAHATANI DIVERSIFIKASI DAN HUBUNGANNYA DENGAN PENDAPATAN USAHATANI KOPI DI SUMATERA SELATAN - Yulian Junaidi; M. Yamin (Publikasi Penelitian Terapan dan Kebijakan, 2020)
This research was objected (1) to investigate factors influencing the adoption of coffee farm diversification ; and (2) to comfare the farm income of diversified coffee cropping pattern with monoculture. The research was conducted on March until November 2007 by survey methode, and data by disproportionate stratifaid random sampling. The total respondens in the research are 90 farmers, its means 30 farmers froms each location (Curup Jare, Fajar Bulan, and Sepatuhu). The group of 30 farmers consisted of 15 farmers planting coffee monoculture and 15 farmers planting coffee diversivication. The result showed that Factors that influencing farmers decision to adopt coffee diversification patern in the production center included income, money capital, production quantty, education level, and experience in farming activities. The significan factors are education level, and experience in farming activities. The farm income of diversified coffee cropping pattern were significantly higher than of coffe monoculture pattern.